Government and politics in Hungary - Körösényi, András (CEU Press ; Osiris, 1999)
Annotation "Based on unprecedented access to information, Government and Politics in Hungary provides not only a historical overview but also an analysis of the main political actors, constitution, electoral system, parliament and political parties of Hungary." "This timely and detailed analysis contains a wealth of important data which serves two major objectives. The first is to survey the most important institutions of the political and governmental systems and the cultural and behavioural characteristics of Hungarian politics. The second, is to provide the reader with a clear understanding of the two-way relationship between cultural-behavioural and constitutional-institutional levels of politics in Hungary." "The book challenges many stereotypes of post-communist political literature and reveals why Hungarian politics does not fit into many of the generalisations and 'pigeon holes' of contemporary political science."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Keywords: Hungary -- Politics and government -- 1989-; Hongrie -- Politique et gouvernement -- 1989-; POLITICAL SCIENCE -- Political Process -- General.; HISTORY -- Europe -- Austria & Hungary.; Politique.; Institutions politiques.; Hongrie.; Politics and government; Hungary; Overheidsbeleid.; Politieke stelsels.; Institutions politiques -- Hongrie.; Hongrie -- Politique et gouvernement -- 1989-.; Since 1989; Constitutional courts, Constitutional law, Political parties, Political studies, Postcommunism.